Evaluate :
(2a-5b) (2a + 5b) (4a² +25b²)
_________________
⚠️ Don't Spam ⚠️
Spam = 10 Ans Report :)
Answers
Answered by
10
ANSWER
(2a-5b) (2a + 5b) (4a² +25b²)
= [(2a - 5b) (2a + 5b)] (4a² + 25b²)
= [(2a)² - (5b)²] (4a² + 25b²)
= (4a² - 25b²) (4a² + 25b²)
= (4a²)² - (25b²)²
= 16a⁴ - 625b⁴ Ans
Answered by
81
- See the above attachment!❤
Thanks!❤
Attachments:
![](https://hi-static.z-dn.net/files/d84/e01892a7f8af84bce0f32d728a52f108.jpg)
Similar questions
Computer Science,
2 months ago
Biology,
2 months ago
English,
4 months ago
Social Sciences,
11 months ago
Math,
11 months ago